A case of amebiasis with negative serologic markers that caused intra-abdominal abscess. Issue 11 (November 2017) - Tanaka, Rie; Furusyo, Norihiro; Takeda, Rinne; Yamasaki, Sho; Kusaga, Akira; Ogawa, Eiichi; Murata, Masayuki; Nakanishi, Ryota; Maehara, Yoshihiko
Abstract: A 23-year-old Japanese woman presented with abdominal distention following fever, diarrhea, and abdominal pain during a stay in Taiwan. Serology for the detection of amebic-antibodies and stool microscopic examination were both negative. A computed tomography scan showed a 13 cm diameter abscess spreading from the lower abdominal wall to the pelvic retroperitoneal space. Needle aspiration of the abscess was done under computed tomography guidance, and microscopy of the aspirated fluid revealed trophozoites of Entamoeba . The patient was diagnosed as amebiasis with negative serologic markers that caused intra-abdominal abscess. Intravenous metronidazole treatment for two weeks did not result in any improvement of the abscess. After irrigation and drainage of the abscess, her symptoms resolved. This case report highlights that amebiasis should be considered when indicated by patient history, including travelers returning from endemic areas, and that further evaluation is necessary for diagnosis, even if the serology and stool test are negative.